An integrated physiological perspective on anthropogenic stressors in the Gulf coast toad (Incilius nebulifer) - Monroe, Dillon J.; Barny, Lea A.; Wu, Alice; Minbiole, Kevin P. C.; Gabor, Caitlin R. (Frontiers in Ecology and Evolution, 2023)
Anthropogenic environmental change, including climate change and urbanization, results in warmer temperatures in both terrestrial and aquatic habitats and changes in community assemblages including invasive species introductions, among many other alterations. Anurans are particularly susceptible to these changes because generally they have a biphasic lifecycle and rely on aquatic and terrestrial habitats for survival. Changes such as warmer water temperature can result in direct and carryover effects, after metamorphosis, that decrease fitness. However, Gulf Coast toads (Incilius (Bufo) nebulifer) are expanding their range, including into anthropogenically disturbed areas. We hypothesize that I. nebulifer copes with warmer water, reduced water levels and invasive species by altering their physiology and/or behavior. Corticosterone is the primary glucocorticoid in amphibians, and it modulates many aspects of physiology and behavior, potentially including lipid storage and hop performance, during unpredictable (stressful) events. As a true toad, I. nebulifer also produces bufadienolide toxins that aid in its antipredator defense and may have tradeoffs with corticosterone. In a fully factorial design, we measured baseline corticosterone levels in tadpoles in response to two treatments: decreased water levels and increased water temperatures. After metamorphosis, we measured the corticosterone profile and other associated responses to exposure to the predatory red imported fire ant (Solenopsis invicta; RIFA). We found that tadpoles had elevated baseline corticosterone release rates when reared in warmer water and reduced water levels. Toadlets also had elevated baseline corticosterone release rates when exposed to any combination of two of the three treatments but when exposed to all three treatments toadlets instead showed elevated magnitude of their stress response. Predator avoidance (as measured by hop performance) was reduced after exposure to RIFA. Tadpoles from warmer water developed more quickly and were smaller in mass after metamorphosis. Toadlets had reduced production of two of the three detected bufadienolides and increased energy storage (lipids) after exposure to warmer water and reduced growth after exposure to reduced water levels. We found direct and carryover effects of common anthropogenic changes in I. nebulifer that may aid in their ability to persist despite these changes.